Analysis of the Relationship Between Architectural Façade Characteristics and Energy Consumption in Educational Buildings (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze the relationship between architectural facade characteristics and energy consumption in educational buildings, and to evaluate the role of different facade elements in improving the building's thermal performance and reducing energy demand. The study employed a hybrid qualitative-analytical methodology, utilizing a literature review to analyze relevant previous studies, a descriptive approach to describe and interpret the data and results, and a quantitative approach to collect, statistically process, and eliminate outliers to ensure the accuracy and reliability of the findings. A simulation methodology using DesignBuilder software, linked to the EnergyPlus engine, was employed to simulate the thermal and energy performance of various architectural facade characteristics. These characteristics included window-to-wall ratio, glass type, thermal insulation properties, facade orientation, and different shading elements. The results indicated a strong, significant relationship between architectural facade characteristics and energy consumption in educational buildings. Improving thermal insulation properties, using high-efficiency glass, and employing appropriate shading systems directly contribute to reducing heat loads and lowering annual energy consumption. The results also showed that window-to-wall ratio and facade orientation are among the most influential factors in a building's energy performance, while advanced shading and insulation solutions have contributed to increased thermal efficiency and improved user comfort. The application of sustainable facade design strategies can lead to energy consumption reductions ranging from 20% to 35% compared to traditional designs. Therefore, the study recommends exploring smart methods and approaches to enhance architectural performance in modern architecture.
Keywords: Architectural facades, energy consumption, educational buildings, various facade elements, thermal performance and energy consumption reduction